2021
DOI: 10.3389/fbioe.2021.749221
|View full text |Cite
|
Sign up to set email alerts
|

Polydopamine Coating-Mediated Immobilization of BMP-2 on Polyethylene Terephthalate-Based Artificial Ligaments for Enhanced Bioactivity

Abstract: Background/objectives: Polyethylene terephthalate (PET)-based artificial ligaments are one of the most commonly used grafts in anterior cruciate ligament (ACL) reconstruction surgery. However, the lack of favorable hydrophilicity and cell attachment for PET highly impeded its widespread application in clinical practice. Studies found that surface modification on PET materials could enhance the biocompatibility and bioactivity of PET ligaments. In this study, we immobilized bone morphogenetic protein-2 (BMP-2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…[ 13 ] PET fibers, which are state‐of‐the‐art synthetic ligaments, are widely used clinically. [ 8a,14 ] After twisting multiple primary composite fibers together, secondary helical fibers (Figure 1e) were obtained, equivalent to the collagen bundles in the native ligament. HCF grafts were successfully fabricated by further twisting and folding the secondary helical fibers (Figure 1b,f).…”
Section: Resultsmentioning
confidence: 99%
“…[ 13 ] PET fibers, which are state‐of‐the‐art synthetic ligaments, are widely used clinically. [ 8a,14 ] After twisting multiple primary composite fibers together, secondary helical fibers (Figure 1e) were obtained, equivalent to the collagen bundles in the native ligament. HCF grafts were successfully fabricated by further twisting and folding the secondary helical fibers (Figure 1b,f).…”
Section: Resultsmentioning
confidence: 99%
“…The study by Kang et al revealed that applying a polydopamine (PDA) coating to immobilize bone morphogenetic protein-2 (BMP-2) on PET artificial ligaments significantly boosts their biocompatibility and bioactivity, ultimately enhancing graft-to-bone healing (Figure 4B). [122] This innovative surface modification approach may lead to improved outcomes in ACLR surgeries utilizing PET-based artificial ligaments. Vaquette investigated the impact of polystyrene sodium sulfonate (PolyNaSS) grafting on the osseointegration of LARS used for ACLR.…”
Section: Tissue Engineering Strategies For Acl Injurymentioning
confidence: 99%
“…As time went by, the droplets gradually infiltrate the scaffolds and the contact angle became smaller. The suitable hydrophilicity of the scaffolds could facilitate cell adhesion, extension, nutrient penetration and factor diffusion, so as to better support the growth of cells (Kang et al, 2021).…”
Section: Wettability Analysismentioning
confidence: 99%